The potential inhibitory effect of ginsenoside Rh2 on mitophagy in UV-irradiated human dermal fibroblasts - Hyunji Lee; Gyeyeong Kong; Jisoo Park; Jongsun Park (Journal of Ginseng Research, 2022)
Background: In addition to its use as a health food, ginseng is used in cosmetics and shampoo because of its extensive health benefits. The ginsenoside, Rh2, is a component of ginseng that inhibits tumor cell proliferation and differentiation, promotes insulin secretion, improves insulin sensitivity, and shows antioxidant effects. Methods: The effects of Rh2 on cell survival, extracellular matrix (ECM) protein expression, and cell differentiation were examined. The antioxidant effects of Rh2 in UV-irradiated normal human dermal fibroblast (NHDF) cells were also examined. The effects of Rh2 on mitochondrial function, morphology, and mitophagy were investigated in UV-irradiated NHDF cells. Results: Rh2 treatment promoted the proliferation of NHDF cells. Additionally, Rh2 increased the expression levels of ECM proteins and growth-associated immediate-early genes in ultraviolet (UV)-irradiated NHDF cells. Rh2 also affected antioxidant protein expression and increased total antioxidant capacity. Furthermore, treatment with Rh2 ameliorated the changes in mitochondrial morphology, induced the recovery of mitochondrial function, and inhibited the initiation of mitophagy in UV-irradiated NHDF cells. Conclusion: Rh2 inhibits mitophagy and reinstates mitochondrial ATP production and membrane potential in NHDF cells damaged by UV exposure, leading to the recovery of ECM, cell proliferation, and antioxidant capacity.